2015
DOI: 10.1007/978-3-319-22368-1_17
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experiments with the Leap Motion as a User Interface in Robotic Endonasal Surgery

Abstract: The Leap Motion controller is a low-cost, optically-based hand tracking system that has recently been introduced on the consumer market. Prior studies have investigated its precision and accuracy, toward evaluating its usefulness as a surgical robot master interface. Yet due to the diversity of potential slave robots and surgical procedures, as well as the dynamic nature of surgery, it is challenging to make general conclusions from published accuracy and precision data. Thus, our goal in this paper is to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
(36 reference statements)
0
12
0
1
Order By: Relevance
“…However, a simulation study of endonasal pituitary surgery that compared the LMC with the Phantom Omni showed that surgeons achieved a percentage of tumour mass resection and procedure duration very similar to that accomplished with the robot using the LMC (104).…”
Section: Discussionmentioning
confidence: 97%
“…However, a simulation study of endonasal pituitary surgery that compared the LMC with the Phantom Omni showed that surgeons achieved a percentage of tumour mass resection and procedure duration very similar to that accomplished with the robot using the LMC (104).…”
Section: Discussionmentioning
confidence: 97%
“…Most of the methods of learning human actions operate at the level of configuration-space trajectories [8] [9] [10]. Some researchers used kinesthetic teaching as the approach to provide demonstrations for a robot to learn from demonstrations [2] [11] [12].…”
Section: Related Workmentioning
confidence: 99%
“…Brown et al [ 73 ] found a take-home laparoscopic instrument simulator for surgical education, while Cobb et al [ 74 ] present a survey on simulation in neurosurgery in connection with the use of the Kinect or LMC sensor. The LMC is used in conjunction with a haptic device (Phantom Omni) within a surgical simulation [ 75 ]. Especially, myographic gesture-control devices, like the Myo-band, will now also be important, for example, as an interaction solution for upper limb amputees [ 76 ] or as an interaction device in a physiotherapy treatment session [ 77 , 78 ].…”
Section: Applications and Contextsmentioning
confidence: 99%